Parents’ Acceptance of Children with Autism Spectrum Disorder (ASD) in Pontianak City - Simangunsong, Glorie Hosiana Maria; Fitrianingrum, Iit; Pratiwi, Sari Eka (Universitas Negeri Malang, 2023)
This study aims to describe parents’ acceptance of children with autism spectrum disorder (ASD) in Pontianak City. The research method used is descriptive with a cross-sectional approach. The research instruments used were the Parental Acceptance-Rejection Questionnaire (PARQ) and the Demographic Data Questionnaire. The respondents who participated in this study were 40 parents, consisting of 16 fathers and 24 mothers. A total of 18 (45 percent) parents accepted, and 22 (55 percent) refused. Most of the respondents were in the category of early middle age (65 percent), married (92 percent), high school graduates (50 percent), housewives/not working (35 percent), and high and very high income (35 percent). The characteristics of parents who accept their child’s condition are early middle age adults, married, high school graduates, housewives/not working, and have moderate-income levels, while the characteristics of parents who refuse are the same as those who accept but have high-income levels. The process of accepting parents who have children with ASD is not easy. Fathers and mothers have different acceptance of children with ASD. Therefore, it is important to know parents’ acceptance of children with ASD starting from the child’s initial diagnosis so that it can help parents make decisions regarding the treatment of children with ASD.